2013
DOI: 10.1111/bld.12006
|View full text |Cite
|
Sign up to set email alerts
|

‘Normal people can have a child but disability can't’: the experiences of mothers with mild learning disabilities who have had their children removed

Abstract: Accessible summary People with learning disabilities might have their children taken from their care. If they do, what then happens to the parents? I talked to nine mums who had their children taken away from their care. They told me about what this was like and how they felt. This research gives advice to people (particularly professional people) about how to work better with mums who have had their children removed. It also shows that sometimes it is difficult for people with learning disabilities to kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…Sixteen papers were rated as “acceptable” (Anslow, ; Brown & Beail, ; Dysch, Chung, & Fox, ; Gould & Dodd, ; Kenyon, Beail, & Jackson, ; MacMahon et al, ; Malik, Unwin, Larkin, Kroese, & Rose, ; McRitchie, McKenzie, Quayle, Harlin, & Neumann, ; Mitchell, Clegg, & Furniss, ; Monteleone & Forrester‐Jones, ; Newberry, Martin, & Robbins, ; Robinson, Escopri, Stenfert Kroese, & Rose, ; Rushbrooke, Murray, & Townsend, ; Shewan, McKenzie, Quayle, & Crawley, ; Sullivan et al, ; Wilson et al, ). All of these papers subscribed to the theoretical principles of IPA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen papers were rated as “acceptable” (Anslow, ; Brown & Beail, ; Dysch, Chung, & Fox, ; Gould & Dodd, ; Kenyon, Beail, & Jackson, ; MacMahon et al, ; Malik, Unwin, Larkin, Kroese, & Rose, ; McRitchie, McKenzie, Quayle, Harlin, & Neumann, ; Mitchell, Clegg, & Furniss, ; Monteleone & Forrester‐Jones, ; Newberry, Martin, & Robbins, ; Robinson, Escopri, Stenfert Kroese, & Rose, ; Rushbrooke, Murray, & Townsend, ; Shewan, McKenzie, Quayle, & Crawley, ; Sullivan et al, ; Wilson et al, ). All of these papers subscribed to the theoretical principles of IPA.…”
Section: Methodsmentioning
confidence: 99%
“…of the papers investigated the experiences of parents with intellectual disabilities(Baum & Burns, 2007;Gould & Dodd, 2014;Shewan et al, 2014;Wilson et al, 2013). Seven of the studies explored the experience of receiving psychological therapy(Anslow, 2013;Lewis et al, 2016;MacDonald et al, 2003;MacMahon et al, 2015;Merriman & Beail, 2009;Roscoe et al, 2016;.…”
mentioning
confidence: 99%
“…Although increased community involvement is assumed to entail a degree of risk as detailed by aforementioned research (e.g., [31][32][33][34]), a number of community stakeholders identified social isolation as a major risk due to a lack of community participation. Although some of this risk may be attributed to geographical location, much is due to social factors.…”
Section: Social Isolationmentioning
confidence: 99%
“…Snyder and colleagues [30] termed people's feelings of decreased self-worth in being part of the community as "devaluation", and in their review of literature on the needs of people with dementia, van der Roest et al [31] identified that the most frequently reported needs of people with dementia are to be accepted and respected as they are, which is not necessarily realistic in terms of being safe and secure in the community. Indeed, there is a plethora of literature focusing on the stigmatic and prejudiced attitudes towards people with an intellectual disability or dementia (e.g., [32][33][34][35]) which undoubtedly contributes to diminished feelings of safety and inclusion in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Mothers with ID frequently report being treated as children, despite being parents, and their abilities are frequently compared to others (Gould & Dodd, 2014). They are often assumed to be incompetent and the result of this was summed up in a quote from research by Gould and Dodd (2014); "normal people can have a child but disability can't." Further, mothers with ID reported never expecting to be exclusively responsible for their child's care (Mayes, Llewellyn, & McConnell, 2011).…”
Section: Womanhoodmentioning
confidence: 99%